Major Incongruence and Occupational Engagement: A Moderated Mediation Model of Career Distress and Outcome Expectation - Kim, Ji Geun; Lee, Ki-Hak (Frontiers in Psychology, 2019)
This study investigated the possible mediation of career distress in the relationship between major incongruence and occupational engagement and whether this mediation depends on the degree of outcome expectation. Moderated mediation analysis was tested on a sample of 346 Korean undergraduate students. The results indicated that career distress mediated the relationship between major incongruence and occupational engagement. Moreover, the negative indirect effect of major incongruence on occupational engagement through career distress weakened as the level of outcome expectation increased. The significant mediation effect of career distress is meaningful given the evidence on the role of emotion in career adaptation. In addition, the significant moderation effect of cognitive evaluation and belief in the mediating relationship on career problem, career emotion, and career behavior is meaningful in that it provides insights in cognitive intervention that could be effective in career counseling.